Hydrophilic core-shell silica gel stationary phase for saccharide component separation as well as preparation method and application of hydrophilic core-shell silica gel stationary phase
By modifying polar groups on the surface of core-shell-type silica gel, hydrophilic core-shell silica gel stationary phase is prepared, and the problems of poor separation and low efficiency of oligosaccharides in traditional Chinese medicine in the prior art are solved, and efficient and excellent oligosaccharide separation effect is achieved.
Patent Information
- Application Number
- CN202411876297.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art has poor separation and low efficiency when isolating oligosaccharides in traditional Chinese medicine, making it difficult to effectively isolate oligosaccharide components with complex structures in traditional Chinese medicine.
Core-shell silica gel modified with polar groups is used as the stationary phase, and core-shell silica gel material with a solid core of 2-2.5 μm and a 150-300 nm thick mesoporous shell layer is prepared, and polar groups such as amide, amino or sulfonic acid are modified on its surface to construct a hydrophilic core-shell silica gel chromatography column.
It has achieved efficient separation of oligosaccharides of traditional Chinese medicine. Compared with traditional chromatography columns, it has higher resolution, better column efficiency, and fast separation speed, which is suitable for quality control of basic research on Chinese medicine quality.
Smart Images

Figure CN119701900A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of separation technology, and in particular relates to a chromatographic separation method for carbohydrate components using a hydrophilic core-shell 2-3 micron silica gel stationary phase, and is particularly applicable to a separation method for oligosaccharides in traditional Chinese medicine, food, and medicine-food homologous products. Background Art
[0002] Oligosaccharides are carbohydrates with straight or branched structures composed of 2 to 10 monosaccharides, and are also a major category of active ingredients in traditional Chinese medicine. Traditional Chinese medicine oligosaccharides have the effects of regulating immunity, anti-depression, tonic, and antioxidant, and are one of the focuses of basic research on traditional Chinese medicine substances. Changes in oligosaccharide composition, such as hydrolysis and cleavage of glycosidic bonds, will change the detector signal. Studying the fingerprint chromatogram of oligosaccharides in traditional Chinese medicine is of great significance to the quality control of traditional Chinese medicine. Due to the complex structure and strong polarity of oligosaccharides, most of them are not well retained and have poor separation on traditional reversed-phase columns during chromatographic separation. In recent years, hydrophilic interaction chromatography (HILIC) columns have been used to separate and analyze the oligosaccharide components of traditional Chinese medicine.
[0003] The existing technologies for liquid chromatography separation of oligosaccharides from traditional Chinese medicines include: Patent CN117946190A uses an XAmide column (4.6*250mm) with an average stationary phase size of 5μm to analyze the oligosaccharides from Morinda officinalis purified by gel chromatography by isocratic elution; Patent CN110845638B uses an XAmide column with a stationary phase particle size of 5μm and a column size of 10*250mm, and uses 66% to 71% v / v acetonitrile aqueous solution as the mobile phase for isocratic elution analysis of the extracted and purified Atractylodes lancea oligosaccharides with different polymerization degrees; Patent CN104215704B uses an ion exchange column proteomix WAX-NP5 (2.1×100mm, 5μm) to analyze honey samples. If oligosaccharide components with a polymerization degree of 6 to 8 are detected, it means that the sample is adulterated honey. In addition to these three examples, there are many chromatographic columns prepared from 2-5 μm fully porous silica modified with hydrophilic or ion exchange groups for separation and analysis of oligosaccharide components. However, due to the variety of monosaccharides that make up oligosaccharides and the diverse linear and branched chain combination structures of oligosaccharides, the current chromatographic analysis has poor separation and low efficiency, which limits the development of oligosaccharide analysis in traditional Chinese medicine.
[0004] The core-shell silica stationary phase is a silica sphere with solid silicon as the core and an ordered mesoporous shell as the shell, and the surface of the mesoporous layer is modified with functional groups to obtain a silica stationary phase. While having the advantages of small particle size filler separation and high efficiency, it can also maintain a low back pressure. In recent years, it has shown good separation performance in rapid separation analysis. Chromatographers have studied and prepared many C18 modified core-shell silica sphere stationary phases with different mesoporous structures. The research on the surface modification of the core-shell silica sphere with C18 groups is the most extensive, but it has little effect on the separation and retention of polar components such as sugars. Secondly, there are core-shell silica modified covalent organic frameworks, metal organic covalent frameworks and other special functional groups, which are used to separate isomers or chiral substances.
[0005] At present, the development of hydrophilic core-shell silica spheres and chromatographic columns is of great significance, especially in the separation of polar compounds. The application of core-shell silica hydrophilic chromatographic columns has great development potential. The present invention provides a core-shell silica stationary phase modified with polar groups and a preparation method thereof for separating Chinese medicine oligosaccharides. Summary of the invention
[0006] The object of the present invention is to provide a chromatographic separation method of a hydrophilic core-shell silica gel stationary phase for use in a carbohydrate component.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] The core-shell silica gel modified with polar groups is used as the stationary phase, which can more efficiently separate and analyze oligosaccharide components compared to traditional 3-5μm fully porous silica gel.
[0009] Preferably, the solid core of the core-shell silica gel material has a size of 2 to 2.5 μm, a mesoporous shell thickness of 150 to 300 nm, a pore size distribution of 7 to 100 nm, and surface polar groups modified to be one or more of amide, amino, and sulfonic acid groups.
[0010] The present invention also provides a method for preparing the hydrophilic core-shell silica gel chromatographic stationary phase material described above, comprising the following steps:
[0011] A. In a three-necked flask, add non-porous silica, urea, hexadecyl sodium bromide (CTAB), sodium bromide, and then add a certain amount of pure water for ultrasonic dissolution and dispersion. Set the water bath temperature to 70°C and the stirring speed to 250rpm. After reacting for 15 minutes, add a certain amount of organic solvent and isopropanol. After reacting for another 15 minutes, add a silicon source and continue to react for 24 hours. The product is washed twice with water and ethanol in turn and then dried. It is calcined in a muffle furnace at 600°C for 6 hours to remove the template and obtain core-shell structure silica. B. Then disperse it in 5% dilute hydrochloric acid, reflux in an oil bath at 120°C for 6 hours, and wash with water and ethanol until neutral.
[0012] 2 g of the activated core-shell silica after drying was dispersed in 30 mL of toluene, 3 mL of silanization agent was added, refluxed at 110 °C for 24 h, and washed twice with methanol to obtain a modified core-shell silica stationary phase.
[0013] C. Add 40 mL of methanol and 15 mL of polar group aqueous solution (0.06 g / mL) for ultrasonic dispersion, set the speed to 250 rpm, stir at a water bath temperature of 65°C for 30 min, add 140 mg of azobisisobutyronitrile, and reflux for 24 h. The product is washed with water and ethanol, and vacuum dried to obtain a hydrophilic core-shell silica suitable for separating Morinda officinalis oligosaccharides.
[0014] Preferably, in step A, the preparation method of the non-porous silica microspheres is: mix water, ethanol, silicon source, and ammonia water, adjust the pH value of the solution to 7-9, add electrolyte, stir continuously for 4-6 hours, let stand, and then obtain silica microspheres by filtering, washing, and drying. The specific addition amount is: when solution A is 22.5mL silicon source and 165mL ethanol, solution B is 21mL water, 227.5mL ethanol, 15.75mL ammonia water and 59mg KCl, and the addition rate of solution A is 31.25mL / h, non-porous silica spheres are obtained, with a mass of about 4g and a particle size range of 1.9-2.3 microns.
[0015] Preferably, in step A, the preparation method of the core-shell silica is: add 3g of non-porous silica balls with a size of 1 to 3.5 microns, 2.025g of hexadecyl sodium bromide, 2.025g of urea, 142.5mL of distilled water, 81mL of xylene, and 3mL of isopropanol into a three-necked flask, ultrasonicate until uniformly dispersed, set the water bath temperature to 70 degrees, add 2mL of silanization agent under stirring, continue stirring for 16 hours, wash with alcohol, dry and calcine at 600 degrees for 6 hours to obtain core-shell silica balls with a shell thickness of 50-300nm.
[0016] Preferably, in step A, the silicon source added during the preparation of the core-shell silica includes one or more of tetraethoxysilane (TEOS), 1,2-bis(triethoxysilyl)ethane (BTEE), and 1,6-bis(triethoxysilyl)hexane (BTMSH).
[0017] Preferably, the hydrochloric acid in step B can be replaced by nitric acid and a mixture thereof, and the silanization agent includes one or more of γ-aminopropyltriethoxysilane (APTES), vinyltriethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
[0018] Preferably, in step C, the surface-modified polar group aqueous solution may be one or more of propane sultone, butane sultone, poly (2-acrylamide-2-methylpropane sulfonic acid), acrylamide, N-hydroxymethyl acrylamide, N-isopropyl acrylamide, and the like.
[0019] The core-shell stationary phase obtained according to the above preparation steps consists of a solid silicon core of 1.5-2.5 μm and a mesoporous hydrophilic layer with vertical pores of 70-300 nm. The pore size of the mesoporous layer is 7-100 nm; the specific surface area of the mesoporous layer is 50-120.2 m 2 The inner diameter of the hydrophilic core-shell chromatographic column is 2.1 or 4.6 mm; the column length is one of 50, 100, and 150 mm, preferably 50 mm.
[0020] The present invention provides a method for preparing a Morinda officinalis oligosaccharide sample, comprising the following steps:
[0021] (a) Morinda officinalis Chinese medicinal material slices were crushed into Morinda officinalis powder using a grinder. (Purchased from Beijing Tong Ren Tang Pharmacy, a chain store) 10 g of medicinal material powder was accurately weighed, 150 mL of pure water was added at a solid-liquid ratio of 1:15, and the mixture was extracted by reflux at 120 degrees in an oil bath for 2 hours, and the filtrate was collected. The residue was added with 150 mL of pure water again and refluxed at 120 degrees for 2 hours, and the two filtrates were collected and combined, and the filtrate was concentrated to 100 mL to obtain the medicinal material water extract concentrate.
[0022] (b) 2 mL of the concentrated aqueous solution was taken and passed through a 0.22-0.45 μm impurity removal water membrane, and then the solution after the membrane was loaded onto a graphitized carbon extraction column (the graphitized carbon extraction column was purchased from AMICRON, model: Carb-GCB adsorbent, particle size range: 100-300 mesh, specific surface area 100 m 2 / g, the filling mass is 90-500mg), 2mL 5% acetonitrile aqueous solution is passed through the extraction column to remove the monosaccharide components, and finally 2mL 50% acetonitrile / water solution is used for repeated elution 3 times to obtain the Morinda officinalis oligosaccharide extract with less monosaccharide content used in the present invention.
[0023] The present invention first prepares a hydrophilic core-shell chromatographic column for separating oligosaccharides, then prepares a sample of the Chinese medicinal material Morinda officinalis oligosaccharide, and finally analyzes the sample according to the following chromatographic separation conditions:
[0024] 2 to 10 L of the prepared Morinda officinalis oligosaccharide sample was injected into the liquid chromatography instrument. The stationary phase in the hydrophilic core-shell column is a core-shell silica sphere with vertical pores modified by polar groups; water is mobile phase A, and acetonitrile is mobile phase B. The mobile phase gradient is 20% A phase and 80% B phase at the beginning of elution, then 0-40min: 80-50% B, 40-50min: 50-75% B. The flow rate is set between 0.3 and 1 mL / min. The detector is an evaporative light scattering detector, and the drift tube temperature is 80-110°C.
[0025] The present invention is based on the preparation of solid silica microspheres and a mesoporous core-shell silica material obtained by in-situ surface growth, and finally the mesoporous shell is modified by simple grafting and polymerization reaction to obtain a hydrophilic core-shell material containing polar groups such as amides. The material of the present invention has a mesoporous pore size of 2-50 nanometers, can separate hydrophilic oligosaccharides, and can separate Morinda officinalis oligosaccharides. Compared with traditional chromatographic columns, the length is reduced, the separation is better, and the column efficiency is higher. The preparation steps of the present invention are simple, the reaction conditions are mild, and the method is simple.
[0026] Advantages of the present invention:
[0027] 1. The present invention applies a hydrophilic core-shell chromatography column to the separation of oligosaccharides from traditional Chinese medicines, providing a new method and idea for the study of the material basis of oligosaccharides from traditional Chinese medicines.
[0028] 2. The present invention is mainly characterized by short chromatographic column length, fast separation speed and high resolution. When separating four standard sugars, the 4.6*5mm chromatographic column is better than the 4.6*150mm fully porous silica packed column modified with polar groups such as hydrothermal carbon and amide. It is also better than the 4.6-5mm chromatographic column of the present embodiment modified with other polar groups of hydrothermal carbon and core-shell silica stationary phase.
[0029] 3. The experimental results of the separation of Morinda officinalis oligosaccharides using the 4.6-5 mm chromatographic column of the present invention showed that the effect was better than that of the commonly used commercial amide column 4.6*150 mm.
[0030] 4. The chromatographic column of the present invention has low pressure and good reproducibility, which is conducive to filling the preparation column to prepare oligosaccharide samples, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 : The transmission electron microscopy and scanning electron microscopy characterization images of the core-shell silicon spheres in Example 1 show obvious core-shell structure and monodispersity, wherein Figure 1 A is a transmission electron microscope image. Figure 1 B is a scanning electron microscope image.
[0032] Figure 2 Example 1: Nitrogen adsorption and desorption curve of core-shell silica microspheres, with a specific surface area of 103.83 m 2 / g,
[0033] Figure 3 : The pore size distribution diagram of the core-shell silicon sphere in Example 1 shows that the average pore size is 16.17 nm and the pore size distribution range is 8-30 nm.
[0034] Figure 4 : Example 1 Schematic diagram of the surface of sulfonic acid-modified core-shell silica spheres, which shows that it is a core-shell structure and the shell layer has hydrophilic sulfonic acid groups.
[0035] Figure 5 : The scanning electron microscopy (a) and element content distribution diagram (b) of the propanesulfonic acid polar group modified core-shell silica gel stationary phase synthesized in Example 1 and the EDX spatial image distribution (c) of C, N, O, Si, and S in the composite material show that nitrogen and sulfur elements are evenly distributed, indicating that the modification is successful.
[0036] Figure 6 : The scanning electron microscope image (a) of the amide-modified core-shell silica sphere stationary phase of Example 2 and the element content diagram (b) and EDX spatial image distribution (c) of C, N, O and Si in the composite material show that the nitrogen element exists and is evenly distributed, and the modification can be successful.
[0037] Figure 7 : Example 1: The chromatogram of standard sugar compounds separated by sulfonic acid core-shell silica sphere stationary phase chromatography shows that the hydrophilic separation of standard oligosaccharides has a retention time of about 23 minutes for stachyose in a 10 cm column.
[0038] Figure 8 : (A) Example 2 amide modified core-shell silica sphere stationary phase in the analysis of Morinda officinalis oligosaccharides and (B) Comparative Example 2 amide porous silica sphere chromatographic separation diagram, it can be seen that the use of a shorter column of 5 cm can achieve better separation results for the same sample under the same mobile phase conditions than the separation results of a longer column of 15 cm, with a higher degree of separation.
[0039] Fig. 9 : Example 3: The chromatogram of the separation of standard sugar compounds using the hydrophilic core-shell silica sphere stationary phase shows that the separation baseline is flat. Under the same conditions, the retention time of stachyose on a 5 cm short column is about 13 minutes.
[0040] Fig.10 : Comparing the chromatogram of the separation of standard sugar compounds by the hydrothermal carbon modified silica porous gel column in Example 1, it can be seen that under the conditions of a 15 cm long, 4.6 mm column and the same mobile phase, the retention time of stachyose is only about 17 minutes. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the examples, which are intended to illustrate the present invention but not to limit the present invention.
[0042] Example 1
[0043] (1) Solution A is composed of a mixture of 22.5 mL of a silicon source (tetraethoxysilane (TEOS)) and 165 mL of ethanol, and solution B is composed of a mixture of 21 mL of water, 227.5 mL of ethanol, 15.75 mL of a 26% concentrated ammonia solution, and 59 mg of KCl. Solution A is added dropwise to solution B under stirring at a rate of 31.25 mL / h. Stirring is continued for 5 hours, and the mixture is allowed to stand. After that, smooth nonporous silica spheres are obtained by filtering, washing, and drying. The spheres have a mass of about 4 g and a particle size range of 1.9-2.3 μm.
[0044] (2) 3 g of the nonporous silica spheres prepared in step (1), 2.025 g of hexadecyl sodium bromide, 2.025 g of urea, 142.5 mL of distilled water, 81 mL of xylene, and 3 mL of isopropanol were added to a three-necked flask, and after being ultrasonically dispersed evenly, the temperature was set to 70 degrees Celsius, and 1.5 mL of TEOS and 0.5 ml of BTEE were added under stirring at 250 rpm. After stirring for 16 hours, the spheres were washed with alcohol, dried, and calcined at 600 degrees Celsius for 6 hours to obtain a shell layer with a thickness of 187.5 nm. The specific surface area was 103.83 m 2 / g, average pore size is 16.17nm, pore size distribution range is 8-30nm. The mesoporous channels are perpendicular to the surface of the non-porous silica sphere.
[0045] (3) 2 g of the core-shell silica spheres prepared in step (2) were dispersed in 30 mL of 5% diluted hydrochloric acid, refluxed in an oil bath at 120° C. for 6 h, washed with water and ethanol in turn until neutral, and dried. 2 g of the dried activated core-shell silica was dispersed in 30 mL of toluene, 3 mL of a silanization agent such as aminopropyltrimethoxysilane was added, refluxed at 110° C. for 24 h, and washed twice with methanol to obtain amino-modified core-shell silica.
[0046] (4) The amino-modified core-shell silica prepared in step (3), 40 mL of methanol, and 15 mL of propane sultone aqueous solution (0.06 g / mL) were ultrasonically dispersed, the speed was set to 250 rpm, the water bath temperature was 65° C., and after stirring for 30 min, 140 mg of azobisisobutyronitrile was added and refluxed for 24 h. The product was washed with water and ethanol in turn, and vacuum dried to obtain a sulfonic acid-modified hydrophilic core-shell silica stationary phase suitable for separating standard oligosaccharides or Morinda officinalis oligosaccharides.
[0047] like Figure 1-5 As shown, through testing, we can know: Figure 1 A and Figure 1 B is the transmission and scanning electron microscopy images, from which it can be seen that the synthesized core-shell silicon sphere has a mesoporous layer with a thickness of 187.5 nm perpendicular to the non-porous core surface. Figure 2This is the nitrogen adsorption curve of the core-shell silicon sphere, which conforms to the type IV isotherm and is an H2-type hysteresis loop, indicating that there is an ordered mesoporous silicon structure on the surface of the silicon sphere. Figure 3 The core-shell silica gel obtained in Example 1 has a simple preparation method, good particle size monodispersity, and uniform pore size distribution, which provides a very good base for the subsequent modification of hydrophilic groups. Figure 4 Schematic diagram of the surface groups of the propane sultone bonded core-shell silica gel stationary phase synthesized in Example 1. Figure 5 The corresponding scanning electron microscope and surface element distribution diagram for the core-shell silica gel fixed with propane sultone. After modification, the shape of the silicon sphere remains good without adhesion. It can be seen that in addition to the oxygen and silicon elements of silicon dioxide, the carbon, nitrogen and sulfur elements are evenly distributed on the surface of the material modified with propane sulfonic acid, and the atomic content percentage accounts for 32.64%.
[0048] Then the stationary phase was filled in a chromatographic column with an inner diameter and length of 4.6mm*100mm, and a standard oligosaccharide mixed aqueous solution consisting of 2mg / mL glucose, 2.1mg / mL maltose, 2mg / mL raffinose, and 2mg / mL stachyose was prepared and loaded; through separation and detection, it was found that when separating the standard oligosaccharides, under the conditions of 1ml / min volume concentration 80% ACN / water (acetonitrile / water) mobile phase, the retention time of stachyose in a 10cm column was about 23 minutes. See attached Figure 7 .
[0049] Example 2
[0050] (1) Synthesis of nonporous silica microspheres Refer to the first step of Example 1 (the process and conditions are the same as those of step (1) of Example 1).
[0051] (2) 3 g of the nonporous silica spheres prepared in step (1) of Example 1, 2.025 g of hexadecyl sodium bromide, 2.025 g of urea, 142.5 mL of distilled water, 81 mL of xylene, and 3 mL of isopropanol were added to a three-necked flask, and after ultrasonication until uniform dispersion, the water bath temperature was set to 70 degrees Celsius, and 2 mL of TEOS was added under stirring. After stirring for 16 hours, the spheres were washed with alcohol, dried, and calcined at 600 degrees Celsius for 6 hours to obtain core-shell silica spheres with a shell thickness of 165 nm. Specific surface area: 103.83 m 2 / g, average pore size 16.17nm, pore size distribution range 8-30nm. The pores are perpendicular to the surface of the non-porous silica sphere.
[0052] (3) 2 g of the core-shell silica spheres prepared in step (2) were dispersed in 30 mL of 1% diluted hydrochloric acid, refluxed in an oil bath at 120° C. for 6 h, washed with water and ethanol in turn until neutral, and dried. 2 g of the dried activated core-shell silica was dispersed in 30 mL of toluene, 3 mL of a silanization agent such as vinyltrimethoxysilane was added, refluxed at 110° C. for 20 h, and washed twice with methanol to obtain vinyl-modified core-shell silica.
[0053] (4) The vinyl-modified core-shell silica prepared in step (3), 40 mL of methanol, and 15 mL of acrylamide aqueous solution (0.06 g / mL) were ultrasonically mixed and dispersed, the speed was set to 250 rpm, the water bath temperature was 65° C., and after stirring for 30 min, 140 mg of azobisisobutyronitrile was added and refluxed for 24 h. The product was washed with water and ethanol in turn, and vacuum dried to obtain an amide-modified hydrophilic core-shell silica stationary phase suitable for separating Morinda officinalis oligosaccharides.
[0054] Through testing, it can be seen that the synthesized core-shell silicon sphere has a mesoporous layer with a thickness of 245nm perpendicular to the non-porous core surface. The nitrogen adsorption curve of the core-shell silicon sphere shows that there is an ordered mesoporous silicon structure on the surface of the silicon sphere. The pore size distribution of the core-shell silicon sphere is calculated, and the maximum pore size distribution is at 16nm. In particular, Figure 6 It can be seen from the scanning electron microscope image and surface element distribution and element content statistics of the amide-modified core-shell silicon spheres in Example 2 that the proportion of N and C elements reached 25.6%, and nitrogen elements were dispersed on each microsphere, confirming that acrylamide was successfully modified on the surface of the core-shell silicon spheres.
[0055] The stationary phase filling column (inner diameter and length are 4.6mm*50mm respectively) verifies its application effect and advantages.
[0056] (5) The processing steps of the Morinda officinalis oligosaccharide sample include the following:
[0057] (a) The Chinese medicinal material slices of Morinda officinalis were crushed into Morinda officinalis powder using a grinder. (Purchased from Beijing Tong Ren Tang Pharmacy, a chain store) Accurately weigh 10g of the medicinal material powder, add 150mL of pure water at a mass ratio of 1:15, extract in an oil bath at 120 degrees Celsius for 2 hours, collect the filtrate, add 150mL of pure water to the residue again and reflux at 120 degrees Celsius for 2 hours, collect and combine the two filtrates, and concentrate the filtrate to 100mL by rotary evaporation to obtain the water extract concentrate of the medicinal material. (b) Take 2mL of the water extract concentrate and pass it through a 0.45μm impurity removal water membrane, then load the solution after the membrane onto a graphitized carbon extraction column (purchased from AMICRON, model: Carb-GCB adsorbent, particle size range: 100-300 mesh, specific surface area 100m 2 / g, the filling mass is 500mg), 2mL of 5% acetonitrile aqueous solution by volume was passed through the extraction column to remove the monosaccharide components, and finally 2mL of 50% acetonitrile aqueous solution was used for repeated elution 3 times to obtain Morinda officinalis oligosaccharide extracts with less monosaccharide content.
[0058] The stationary phase was filled in a chromatographic column with an inner diameter and length of 4.6 mm*50 mm, and the Morinda officinalis oligosaccharide extract was loaded; through separation and detection, it was found that under the condition of 1 ml / min volume concentration 80% ACN / water (acetonitrile / water) mobile phase, the results were specifically as follows: Figure 8 A. The mixed solution of Morinda officinalis oligosaccharides obtained complete baseline separation, column efficiency, and resolution. The results are listed in Table 1. It can be seen that the shorter column of the stationary phase is 5 cm long, which can separate the same sample better than the longer column of 15 cm under the same mobile phase conditions, and the resolution is higher.
[0059] Example 3
[0060] (1) The synthesis of non-porous silica is the same as that of step (1) of Example 1, except that solution A is composed of 10.8 mL TEOS and 79.2 mL ethanol, and solution B is composed of 9.6 mL water, 104 mL ethanol, 7.4 mL ammonia with a mass concentration of 26%, and 27 mg KCl. Solution A is added dropwise to solution B under stirring. When the addition rate of solution A is 15 mL / h, stirring is continued for 4 to 6 hours (here 5 hours), and then allowed to stand. After that, non-porous silica of about 2.5 g is obtained by filtering, washing, and drying. The particle size range is 1.7-2.1 μm;
[0061] (2) 3 g of the nonporous silica spheres prepared in step (1), 2.025 g of hexadecyl sodium bromide, 2.025 g of urea, 142.5 mL of distilled water, 81 mL of toluene, and 3 mL of isopropanol were added to a three-necked flask, and after being ultrasonically dispersed, the water bath temperature was set to 70 degrees Celsius, and 2 mL of TEOS was added under stirring. After stirring for 16 hours, the spheres were washed with alcohol, dried, and calcined at 600 degrees Celsius for 6 hours to obtain core-shell silica spheres with a shell thickness of 340 nm. The specific surface area was 96.13 m 2 / g, average pore size is 36.49nm, pore size distribution range is 10-120nm. The pores are perpendicular to the surface of the non-porous silica sphere.
[0062] (3) 2.5 g of the core-shell silica spheres prepared in step (2) were dispersed in 60 mL of 2% diluted hydrochloric acid, refluxed in an oil bath at 120° C. for 6 h, washed with water and ethanol until neutral, and dried. 2 g of the dried activated core-shell silica was dispersed in 30 mL of toluene, 3 mL of a silanization agent such as chloropropyltrimethoxysilane was added, refluxed at 110° C. for 24 h, and washed twice with methanol to obtain chloropropyl-modified core-shell silica.
[0063] (4) Ultrasonic dispersion of the chloropropyl-modified core-shell silica obtained in step (3), 40 mL of methanol, and 15 mL of polyethyleneimine aqueous solution (0.06 g / mL), with the rotation speed set at 250 rpm and the water bath temperature at 65°C for 30 min, followed by addition of 140 mg of azobisisobutyronitrile and reflux for 24 h. The product was washed with water and ethanol in turn, and vacuum dried to obtain a sulfonic acid-modified polyamino-modified hydrophilic core-shell silica stationary phase suitable for separating Morinda officinalis oligosaccharides.
[0064] Through testing, it can be seen that the synthesized core-shell silicon sphere has a mesoporous layer with a thickness of 340nm perpendicular to the non-porous core surface. The nitrogen adsorption curve of the core-shell silicon sphere shows that there is an ordered mesoporous silicon structure on the surface of the silicon sphere. The pore size distribution of the core-shell silicon sphere is calculated, and the maximum pore size distribution is at 36.49nm. The specific surface area is 96.13m 2 / g Especially after modification, the shape of the silicon spheres remains good without adhesion. And it can be seen that in addition to the oxygen and silicon elements of silicon dioxide, the carbon and nitrogen elements are also evenly distributed on the surface of the material modified by propanesulfonic acid, and the atomic content percentage accounts for 38.14%.
[0065] The stationary phase was filled in a chromatographic column with an inner diameter and length of 4.6 mm*50 mm, and a separation test was performed on a standard sugar sample. The standard sugar preparation method and the loading and elution process and conditions were the same as those in Example 1. The separation results showed a higher resolution and a higher retention time of stachyose. Fig. 9 shown.
[0066] Example 4
[0067] (1) The synthesis of non-porous silica is the same as that of step (1) of Example 1, except that solution A is composed of 10.8 mL TEOS and 79.2 mL ethanol, and solution B is composed of 9.6 mL water, 104 mL ethanol, 7.4 mL ammonia with a mass concentration of 26%, and 27 mg KCl. Solution A is added dropwise to solution B under stirring. When the addition rate of solution A is 15 mL / h, stirring is continued for 4 to 6 hours (here 5 hours), and then allowed to stand. After that, non-porous silica of about 2.5 g is obtained by filtering, washing, and drying. The particle size range is 1.8-2.3 μm;
[0068] (2) 3 g of nonporous silica spheres obtained in step (1), 2.025 g of hexadecyl sodium bromide, 2.025 g of urea, 142.5 mL of distilled water, 81 mL of xylene, and 3 mL of isopropanol were added to a three-necked flask, and after being ultrasonically dispersed, the water bath temperature was set to 70 degrees Celsius, and 3 mL of TEOS was added under stirring. After stirring for 16 hours, the spheres were washed with alcohol, dried, and calcined at 600 degrees Celsius for 6 hours to obtain core-shell silica spheres with a shell thickness of 245 nm. The specific surface area was 68.16 m 2 / g, average pore size 21.65nm, pore size distribution range 8-100nm. The pores are perpendicular to the surface of the non-porous silica sphere.
[0069] (3) The core-shell silica spheres prepared in step (2) were dispersed in 30 mL of 5% dilute nitric acid, refluxed in an oil bath at 120°C for 6 h, washed with water and ethanol in turn until neutral, and dried. 2 g of the dried activated core-shell silica was dispersed in 30 mL of toluene, 3 mL of a silanization agent such as vinyl trimethoxysilane was added, refluxed at 110°C for 24 h, and washed with methanol twice to obtain vinyl-modified core-shell silica. (4) The vinyl-modified core-shell silica prepared in step (3), 40 mL of methanol, and 15 mL of 2-acrylamido-2-methylpropanesulfonic acid aqueous solution (0.06 g / mL) were ultrasonically mixed and dispersed, the speed was set to 250 rpm, the water bath temperature was 65°C, and after stirring for 30 min, 140 mg of azobisisobutyronitrile was added and refluxed for 24 h. The product was washed with water and ethanol in turn, and vacuum dried to obtain amide and sulfonic acid modified hydrophilic core-shell silica suitable for separating Morinda officinalis oligosaccharides.
[0070] Through testing, it can be seen that the synthesized core-shell silicon sphere has a mesoporous layer with a thickness of 245nm perpendicular to the non-porous core surface. The nitrogen adsorption curve of the core-shell silicon sphere shows that there is an ordered mesoporous silicon structure on the surface of the silicon sphere. The specific surface area is 68.16m 2 / g. The pore size distribution of the core-shell silicon spheres was calculated, and the maximum pore size distribution was at 21.65nm. After modification, the morphology of the silicon spheres remained good without adhesion. It can be seen that in addition to the oxygen and silicon elements of silicon dioxide, the carbon, nitrogen and sulfur elements are evenly distributed on the surface of the material modified by propanesulfonic acid, and the atomic content percentage accounts for 29.24%.
[0071] The stationary phase filling specifications, the Morinda officinalis oligosaccharide sample preparation method, and the sample loading and elution process and conditions were the same as those in Example 2. The results showed that the separation degree was higher than that in Example 2, and the number of obtained compounds was more than that in Example 2.
[0072] Example 5
[0073] (1) The synthesis of non-porous silica is the same as that of step (1) of Example 1, except that solution A is composed of 10.8 mL TEOS and 79.2 mL ethanol, and solution B is composed of 9.6 mL water, 104 mL ethanol, 7.4 mL ammonia with a mass concentration of 26%, and 27 mg KCl. Solution A is added dropwise to solution B under stirring. When the addition rate of solution A is 15 mL / h, stirring is continued for 4 to 6 hours (here 5 hours), and then allowed to stand. After that, non-porous silica of about 2.5 g is obtained by filtering, washing, and drying. The particle size range is 1.7-2.1 μm;
[0074] (2) Take 2.5g of non-porous silica balls, 4.05g of hexadecyl sodium bromide, 4.05g of urea, 283mL of distilled water, 160mL of xylene, and 6mL of isopropanol in step (1) and add them into a three-necked flask. After ultrasonication until uniform dispersion, the water bath temperature is set to 70 degrees Celsius. Under stirring, 2mL of TEOS and 0.75ml of a bridging silanization agent, BTMSH, are added. After stirring for 16 hours, the mixture is washed with alcohol, dried, and calcined at 600 degrees Celsius for 6 hours to obtain core-shell silicon balls with a shell thickness of 75nm. The specific surface area is 37.53m 2 / g, average pore size 17.93nm, pore size distribution range 10-70nm. The pores are perpendicular to the surface of the non-porous silica sphere.
[0075] (3) The core-shell silica spheres obtained in step (2) were dispersed in 50 mL of 2% dilute nitric acid, refluxed in an oil bath at 120° C. for 6 h, washed with water and ethanol until neutral, and dried. 2 g of the dried activated core-shell silica was dispersed in 60 mL of toluene, 6 mL of a silanization agent such as vinyltrimethoxysilane was added, refluxed at 120° C. for 14 h, and washed twice with methanol to obtain vinyl-modified core-shell silica.
[0076] (4) The vinyl-modified core-shell silica obtained in step (3), 80 mL of methanol, and 30 mL of N-hydroxymethyl acrylamide (0.08 g / mL) were ultrasonically mixed and dispersed, the speed was set to 350 rpm, the water bath temperature was 65° C., and after stirring for 30 min, 200 mg of azobisisobutyronitrile was added and refluxed for 24 h. The product was washed with water and ethanol in turn, and vacuum dried to obtain an amide-modified hydrophilic core-shell silica stationary phase suitable for separating Morinda officinalis oligosaccharides.
[0077] The results show that the synthesized core-shell silicon sphere has a mesoporous layer with a thickness of 75 nm perpendicular to the non-porous core surface. The nitrogen adsorption curve of the core-shell silicon sphere shows that there is an ordered mesoporous silicon structure on the surface of the silicon sphere. The specific surface area is 37.53 m 2 / g. The pore size distribution of the core-shell silicon spheres was calculated, and the maximum pore size distribution was at 17.93nm. After modification, the morphology of the silicon spheres remained good without adhesion. It can be seen that in addition to the oxygen and silicon elements of silicon dioxide, the carbon and nitrogen elements on the surface of the material modified by propanesulfonic acid are evenly distributed, and the atomic content percentage accounts for 28.1%.
[0078] The stationary phase filling specifications, the sample preparation method of the standard tetrasaccharide, the loading and elution process and conditions are the same as those in Example 1. Specifically, it can be found that the retention time of stachyose is 21 minutes, the peak shapes of the four sugars are more symmetrical, and the separation degree is higher than that in Example 1.
[0079] Comparative Example 1
[0080] Preparation of hydrothermal carbon material modified porous silica gel hydrophilic stationary phase and chromatographic column filling:
[0081] The process and conditions are the same as in Example 1, both of which are the preparation of hydrophilic stationary phases and the comparison of their application effects on the separation of oligosaccharides. The preparation of the samples is the same. The difference is that in steps 1-3 of Example 1, the present invention prepares a core-shell silica matrix stationary phase. Comparative Example 1 is to choose to buy a silica stationary phase matrix (purchased from Shanxi Zhiwei Technology Co., Ltd.) The silica gel specifications selected are commonly used specifications (silicon sphere particle size 3 to 5 μm (average particle size 4 μm), pore size is fully porous 7 to 12 nm (average pore size 9 nm); specific surface area is 200 to 300 m 2 / g (here 260m 2 / g), both are conventional matrix materials). The difference 2 is that the preparation method of the hydrophilic material prepared by modifying the hydrophilic groups on the surface of silicon dioxide is different.
[0082] The preparation of modified fully porous silica gel is as follows (reference: Journal of Chromatography A, 1585 (2019) 144–151), 4 g of cyclodextrin is weighed into a reactor with a polytetrafluoroethylene liner, 2 g of PVP (polyvinyl pyrrolidone) and 100 mL of deionized water are added, and the mixture is placed in an oven at 100°C for 30 minutes. After the solution is clarified, 2 g of the above-mentioned silica is added, stirred evenly, and the reactor is removed after reacting at 200°C in an oven for 6 hours, cooled to room temperature, and the material is washed with deionized water and ethanol 5 times each until the supernatant is transparent, and the solid material is placed in an oven at 80°C for vacuum drying for 6 hours to obtain the cyclodextrin hydrothermal carbon microsphere stationary phase.
[0083] The stationary phase is filled with a chromatographic column (inner diameter and length are 4.6 mm*150 mm, Fig.10 ) and the propane sultone modified core-shell silica gel stationary phase packed column of Example 1 of the present invention (inner diameter and length are 4.6 mm*100 mm, respectively, Figure 7) and the hydrophilic amino-modified core-shell silica gel stationary phase packed column (inner diameter and length 4.6 mm*50 mm, respectively, as in Example 3 of the present invention) Fig. 9 )Comparison of separation methods and performance for separation of standard oligosaccharides.
[0084] The sample preparation method and sample loading and elution process and conditions of the standard tetrasaccharide are the same as those in Example 1. Under the mobile phase condition of 1 ml / min volume concentration 80% ACN / water (acetonitrile / water), it can be seen that the retention strength of stachyose is not as good as that in Example 1. The specific result is that the retention time of stachyose is 17 minutes.
[0085] Comparative Example 2
[0086] Similar to Example 2, both are the preparation of hydrophilic stationary phase and the comparison of its application effect on oligosaccharide separation. The preparation of samples is the same.
[0087] The process and conditions are the same as those of Example 2, except that the materials prepared in steps (1) and (2) of Example 2 are silica gel of commonly used specifications (silicon sphere particle size 2-4 μm, pore size 7-12 nm; specific surface area 200-300 m 2 / g (here 260m 2 / g), both of which are conventional matrix materials), without performing steps (1) and (2), and directly performing steps (3) and (4) using the above silicon spheres.
[0088] Specifically:
[0089] (3) 2 g of the above silicon spheres were dispersed in 30 mL of 1% mass concentration dilute hydrochloric acid, refluxed in an oil bath at 120° C. for 6 h, washed with water and ethanol in turn until neutral, and dried. 2 g of the dried activated core-shell silica was dispersed in 30 mL of toluene, 3 mL of a silanization agent such as vinyltrimethoxysilane was added, refluxed at 110° C. for 20 h, and washed twice with methanol to obtain vinyl-modified silica.
[0090] (4) The vinyl-modified silica prepared in step (3), 40 mL of methanol, and 15 mL of acrylamide aqueous solution (0.06 g / mL) were ultrasonically mixed and dispersed, the speed was set to 250 rpm, the water bath temperature was 65° C., and after stirring for 30 min, 140 mg of azobisisobutyronitrile was added and refluxed for 24 h. The product was washed with water and ethanol in turn, and vacuum dried to obtain an amide-modified hydrophilic silica stationary phase suitable for separating Morinda officinalis oligosaccharides.
[0091] The results show that the synthesized amide silica spheres have a particle size of 2-4 μm, a pore size of 7-20 nm, and a specific surface area of 210 m 2 / g, the nitrogen adsorption curve of the core-shell silicon sphere shows that there is a mesoporous silicon structure on the surface of the silicon sphere. The pore size distribution of the core-shell silicon sphere is calculated, and the maximum pore size distribution is at 13nm. In particular, the scanning electron microscope image and surface element distribution and element content statistics of the amide-modified silicon sphere show that the proportion of N and C elements reaches 27.6%, and the nitrogen element is dispersed on each microsphere, which confirms that acrylamide has successfully modified the surface of the purchased silicon sphere.
[0092] (5) The processing steps of the Morinda officinalis oligosaccharide sample include the following:
[0093] (a) Morinda officinalis Chinese medicinal material slices were crushed into Morinda officinalis powder using a pulverizer. (Purchased from Beijing Tongrentang Pharmacy, a chain store) 10 g of medicinal material powder was accurately weighed, and 150 mL of pure water was added at a mass ratio of 1:15. After reflux extraction at 120 degrees Celsius oil bath for 2 hours, the filtrate was collected, and the residue was added with 150 mL of pure water again and refluxed at 120 degrees Celsius for 2 hours. The filtrates of the two times were collected and combined, and the filtrate was concentrated by rotary evaporation to 100 mL to obtain the water-extracted concentrate of the medicinal material.
[0094] (b) 2 mL of the concentrated aqueous solution was taken and passed through a 0.45 μm impurity removal water membrane. The solution after passing through the membrane was then loaded onto a graphitized carbon extraction column (purchased from AMICRON, model: Carb-GCB adsorbent, particle size range: 100-300 mesh, specific surface area 100 m 2 / g, the filling mass is 500mg), 2mL of 5% acetonitrile aqueous solution by volume concentration is passed through the extraction column to remove the monosaccharide components, and finally 2mL of 50% acetonitrile aqueous solution by volume concentration is repeatedly eluted 3 times to obtain the Morinda officinalis oligosaccharide extract with less monosaccharide content of the sample used in the present invention.
[0095] The stationary phase packed column (inner diameter and length are 4.6mm*150mm, Figure 8 B) and the amide-modified core-shell silica gel stationary phase packed column (inner diameter and length 4.6 mm*50 mm, respectively, of Example 2 of the present invention; Figure 8 A) Comparison of separation methods and performance of isolating Morinda officinalis oligosaccharides.
[0096] The sample loading and elution process and conditions are the same as those in Example 2. It can be seen that the separation degree and column efficiency are not as good as those in Example 2. The specific result is that the separation degree of compound 5 and compound 6 is 1.69. The separation degree of the compound in Example 2 of the present invention and compound 6 is 2.85. For specific data, see Figure 8 and Table 1. Comparative Example 3: Preparation of hydrothermal carbon material modified core-shell silica stationary phase and chromatographic column filling:
[0097] The process and conditions are the same as those in Example 1, both of which are the preparation of hydrophilic stationary phases and the comparison of their application effects on oligosaccharide separation. The sample preparation is the same. The difference is that in Example 1, steps 1-3 are hydrophilic stationary phases obtained by modifying the core-shell silica matrix prepared by the present invention with sulfonic acid polar groups. Comparative Example 3 is modified with other polar groups such as hydrothermal carbon. The process and conditions of steps (1)-(2) are the same as those of steps (1)-(2) in Example 1.
[0098] (1) Solution A is composed of 22.5 mL of silicon source (tetraethoxysilane (TEOS)) and 165 mL of ethanol, and solution B is composed of 21 mL of water, 227.5 mL of ethanol, 15.75 mL of 26% ammonia water and 59 mg of KCl. Solution A is added dropwise to solution B under stirring. When the addition rate of solution A is 31.25 mL / h, stirring is continued for 4 to 6 hours (here 5 hours), and the mixture is allowed to stand. After that, smooth non-porous silica spheres are obtained by filtering, washing and drying. The mass of the spheres is about 4 g and the particle size range is 1.9-2.3 μm.
[0099] (2) 3 g of the nonporous silica spheres prepared in step (1), 2.025 g of hexadecyl sodium bromide, 2.025 g of urea, 142.5 mL of distilled water, 81 mL of xylene, and 3 mL of isopropanol were added to a three-necked flask, and after being ultrasonically dispersed evenly, the temperature was set to 70 degrees, and 1.5 mL of TEOS and 0.5 ml of BTEE were added under stirring at 250 rpm. After stirring for 16 hours, the spheres were washed with alcohol, dried, and calcined at 600 degrees for 6 hours to obtain a shell layer with a thickness of 187.5 nm. The specific surface area was 103.83 m 2 / g, average pore size 16.17nm, pore size distribution range 8-30nm. The pores are perpendicular to the surface of the non-porous silica sphere.
[0100] The difference between step 3-4 is that it is prepared as follows (reference: Journal of Chromatography A, 1585 (2019) 144–151), 4 g of cyclodextrin is weighed into a reactor with a polytetrafluoroethylene liner, 2 g of PVP (polyvinyl pyrrolidone) and 100 mL of deionized water are added, and the reaction is carried out in an oven at 100 ° C for 30 minutes. After the solution is clarified, 2 g of silica is added (the shell thickness is 187.5 nm. The specific surface area is 103.83 m 2 / g, average pore size 16.17nm, pore size distribution range 8-30nm. The pores are perpendicular to the surface of the non-porous silica sphere), stir evenly, react in an oven at 200℃ for 6 hours, take out the reactor, cool to room temperature, wash the material with deionized water and ethanol 5 times each until the supernatant is transparent, put the solid material into an oven at 80℃ vacuum drying for 6 hours to obtain the cyclodextrin hydrothermal carbon microsphere stationary phase.
[0101] Through testing, it can be known that the synthesized hydrothermal carbon modified core-shell silicon spheres, the nitrogen adsorption curve shows that the silicon spheres have a mesoporous silicon structure. The pore size distribution of the core-shell silicon spheres was calculated, and the maximum pore size distribution was at 18nm. In particular, the scanning electron microscope image and surface element distribution and element content statistics of the amide-modified silicon spheres measured showed that the proportion of N and C elements reached 35.8%, and the nitrogen element was dispersed on each microsphere, confirming that the hydrothermal carbon was successfully modified on the surface of the core-shell silicon spheres.
[0102] The stationary phase filling specifications, the sample preparation method of the standard tetrasaccharide, and the loading and elution process and conditions are the same as those in Example 1. The separation method and performance of separating standard oligosaccharides are compared, and the results show that the separation degree is not as good as that of Example 1 of the present invention. The results specifically show that under the same mobile phase conditions of acetonitrile water, the retention time of stachyose is smaller and the chromatographic separation degree is smaller.
[0103] Comparative Example 4
[0104] Preparation of fully porous silica stationary phase with similar particle size and pore size modified by amide polar groups and chromatographic column filling: The process and conditions are the same as in Example 2, both of which are preparation of hydrophilic stationary phase and comparison of its application effect on oligosaccharide separation. The preparation of samples is the same. The difference is that steps 1-3 in Example 2 are hydrophilic stationary phases obtained by modifying the core-shell silica matrix prepared by the present invention with amide polar groups.
[0105] Comparative Example 4 is an amide-modified non-core-shell silica stationary phase. Step 1-2 is different from that of Example 2: Steps (1) and (2) are changed to:
[0106] (1) 10.15 g urea, 5 g K2SO4, 68 mL sol composed of 5-20 nm mass concentration 20% silicon nanoparticles, and 15 mL mass concentration 1% Tween were added to water, the pH value of the solution was adjusted to 1-2 with concentrated hydrochloric acid, 12.6 mL formaldehyde was added, and the mixture was stirred continuously for 10-15 minutes (here 12 minutes). The reaction system was allowed to stand for a period of time, the supernatant was poured or discharged by filtering and washing, and dried to obtain silica microspheres;
[0107] (2) The silicon dioxide obtained in step (1) was dried and calcined at 600 degrees for 6 hours to obtain a particle size equivalent to that of the embodiment of the present invention, about 2-3 microns, and a specific surface area of 140 m 2 / g, fully porous silica material with pore size ranging from 5-30nm)
[0108] Steps 3-4 are the same as in Example 2, and are prepared as follows:
[0109] (3) 2 g of the porous silicon spheres prepared in step (2) were dispersed in 30 mL of 1% diluted hydrochloric acid, refluxed in an oil bath at 120° C. for 6 h, washed with water and ethanol in turn until neutral, and dried. 2 g of the dried activated core-shell silica was dispersed in 30 mL of toluene, 3 mL of a silanization agent such as vinyltrimethoxysilane was added, refluxed at 110° C. for 20 h, and washed twice with methanol to obtain vinyl-modified porous silica.
[0110] (4) The vinyl-modified porous silica prepared in step (3), 40 mL of methanol, and 15 mL of acrylamide aqueous solution (0.06 g / mL) were ultrasonically mixed and dispersed, the speed was set to 250 rpm, the water bath temperature was 65°C, and after stirring for 30 min, 140 mg of azobisisobutyronitrile was added and refluxed for 24 h. The product was washed with water and ethanol in turn, and vacuum dried to obtain an amide-modified hydrophilic porous silica stationary phase suitable for separating Morinda officinalis oligosaccharides.
[0111] Through testing, it can be known that the nitrogen adsorption curve of the synthesized hydrophilic porous silicon spheres shows that the silicon spheres have a mesoporous silicon structure. The pore size distribution of the core-shell silicon spheres was calculated, and the maximum pore size distribution was at 14nm. In particular, the scanning electron microscope images and surface element distribution and element content statistics of the amide-modified silicon spheres measured showed that the proportion of N and C elements reached 25.6%, and the nitrogen element was dispersed on each microsphere, confirming that acrylamide was successfully modified on the surface of the porous silicon spheres.
[0112] (5) The processing steps of the Morinda officinalis oligosaccharide sample include the following:
[0113] (a) The Chinese medicinal material slices of Morinda officinalis were crushed into Morinda officinalis powder using a grinder. (Purchased from Beijing Tong Ren Tang Pharmacy, a chain store) Accurately weigh 10g of the medicinal material powder, add 150mL of pure water at a mass ratio of 1:15, extract in an oil bath at 120 degrees Celsius for 2 hours, collect the filtrate, add 150mL of pure water to the residue again and reflux at 120 degrees Celsius for 2 hours, collect and combine the two filtrates, and concentrate the filtrate to 100mL by rotary evaporation to obtain the water extract concentrate of the medicinal material. (b) Take 2mL of the water extract concentrate and pass it through a 0.45μm impurity removal water membrane, then load the solution after the membrane onto a graphitized carbon extraction column (purchased from AMICRON, model: Carb-GCB adsorbent, particle size range: 100-300 mesh, specific surface area 100m 2 / g, the filling mass is 500mg), 2mL of 5% acetonitrile aqueous solution by volume was passed through the extraction column to remove the monosaccharide components, and finally 2mL of 50% acetonitrile aqueous solution was used for repeated elution 3 times to obtain Morinda officinalis oligosaccharide extracts with less monosaccharide content.
[0114] The stationary phase filling column (inner diameter and length are 4.6mm*50mm respectively) verifies its application effect and advantages.
[0115] The sample loading and elution process and conditions are the same as those in Example 2. The specific results are to compare the separation method and performance of separating Morinda officinalis oligosaccharides. The results show that the separation degree is not as good as the amide group modified core-shell silica stationary phase in Example 2 of the present invention. The separation degree and column efficiency of the compound separation are not as good as the stationary phase in Example 2.
[0116] The hydrophilic core-shell stationary phase of the present invention is connected to the surface of the vertical pores of the core-shell silica gel. Figure 6 Polar groups shown. The experimental conditions for separating standard sugars in Examples 1, 2, 3 and Comparative Examples 1 and 2 are as follows: Mobile phase conditions: 80% acetonitrile / water by volume. The flow rate is 1 ml per minute. Detector and its parameters: Shanghai Tongwei evaporative light scattering detector; evaporation temperature: 80°C; compressed air flow rate: 2.6 L / min. The sample composition is: (1) glucose (2 mg / mL), (2) maltose (2.1 mg / mL), (3) raffinose (2 mg / mL), (4) stachyose (2 mg / mL).
[0117] The separation method for oligosaccharide components in the complex sample Morinda officinalis is as follows: mobile phase A: water, B: acetonitrile. Gradient elution: 0-40min: 80-50% B, 40-50min: 50-75% B. Flow rate: 1 ml per minute, detector and its parameters: Shanghai Tongwei evaporative light scattering detector; evaporation temperature: 80℃; compressed air flow: 2.6L / min.
[0118] Table 1 Comparison of separation parameters of Morinda officinalis oligosaccharides
[0119]
[0120] Table 1 lists the chromatographic parameter data of the amide-modified core-shell chromatographic column of Example 2 of the present invention and the chromatographic column of Comparative Example 2 under the same mobile phase and gradient, wherein the column efficiency, peak width and other data are the results after gradient analysis compression, which are only discussed and compared here. It can be seen that the column efficiency and separation degree of the core-shell chromatographic column are higher, and the analysis time is saved more. This also proves that the hydrophilic core-shell chromatographic column has certain application advantages in analyzing complex oligosaccharide samples in traditional Chinese medicine extracts.
Claims
1. A method for preparing a hydrophilic core-shell silica gel stationary phase for separating carbohydrate components, characterized in that: Here are the steps: A. In a container, add non-porous silica with a particle size of 1.5-2.5 μm, urea, hexadecyl sodium bromide (CTAB), and water, and disperse and mix them evenly; add organic solvent and isopropanol, set the temperature to 50-90°C, set the stirring speed to 250-550rpm, react for 10-30 minutes, add silicon source, and continue to react for 12-48 hours; wash the product with water and ethanol in turn, then dry it, calcine it in a muffle furnace at 500-700°C for 3-8 hours to remove the template, and obtain core-shell structure silica; B. Then 2-5g of core-shell silica is dispersed in 30-90mL of one or a mixture of dilute hydrochloric acid or nitric acid with a mass concentration of 0.01-5%, refluxed in an oil bath at 110-120°C for 6-24h, washed with water and ethanol in turn until neutral, and dried to obtain activated core-shell silica; 2-5 g of the dried activated core-shell silica is dispersed in 30-300 mL of toluene, 1-20 mL (preferably 1-5 mL) of a silanization agent is added, refluxed at 110-120° C. for 12-24 h, and washed with methanol to obtain a modified core-shell silica stationary phase; C. Add 40-100 mL of methanol and 1-15 mL of polar group aqueous solution (0.01-0.1 g / mL) to the modified core-shell silica stationary phase for ultrasonic dispersion again, set the speed to 250-550 rpm, stir at 65-85 °C for 20-60 min, add 40-280 mg of azobisisobutyronitrile, and reflux for 10-24 h; wash the product with water and ethanol in turn, and obtain a hydrophilic core-shell silica stationary phase after drying.
2. The preparation method according to claim 1, characterized in that: The preparation process of the non-porous silica microspheres described in step A is as follows: water, ethanol, silicon source, and ammonia water are mixed in the order of (4-100 ml): (50-500 ml): (4-45 mL): (3-30 mL), the pH value of the solution is adjusted to 7-9, 20-200 mg of electrolyte potassium chloride is added, stirring is continued for 4-6 hours, and the mixture is allowed to stand, and then the silica microspheres are obtained by filtering, washing, and drying; the obtained non-porous silica particles have a particle size range of 1-3.5 microns (preferably 1.5-2.5 microns).
3. The preparation method according to claim 1, characterized in that: In step A, the material ratio is preferably: 1-5 g of non-porous silica balls with a particle size of 1-3.5 microns (preferably 1.5-2.5 microns), 2.025-4.05 g of hexadecyl sodium bromide, 2.025-4.05 g of urea, 142.5-285 mL of water, 20-200 mL of an organic solvent xylene, and 1-6 mL of isopropanol are added to a container; 2-10 mL of a silicon source reagent is added under stirring, stirring is continued for 2-16 hours, and then washed, dried, and calcined at 500-700° C. for 3-8 hours to obtain core-shell silicon balls with a shell thickness of 60-300 nm.
4. The preparation method according to claim 2 or 3, characterized in that: In step A, the silicon source added during the preparation of the core-shell silica includes one or more of tetraethoxysilane (TEOS), 1,2-bis(triethoxysilyl)ethane (BTEE), and 1,6-bis(triethoxysilyl)hexane (BTMSH).
5. The preparation method according to claim 1, characterized in that: The silanization agent described in step B includes one or more of γ-aminopropyltriethoxysilane (APTES), vinyltriethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.
6. The preparation method according to claim 2, characterized in that: In step C, the polar group aqueous solution is an aqueous solution of one or more of acrylamide, propane sultone, butane sultone, poly-2-acrylamide-2-methylpropane sulfonic acid, N-hydroxymethyl acrylamide, and N-isopropyl acrylamide.
7. A hydrophilic core-shell silica gel stationary phase obtained by the method according to any one of claims 1 to 6, characterized in that: The core-shell stationary phase is composed of a solid silicon core with a particle size of 1 to 3.5 microns (preferably a particle size of 1.5 to 2.5 μm) and a hydrophilic mesoporous layer with a thickness of 70 to 300 nm (preferably 150 to 300 nm) and mesoporous channels perpendicular to the surface of the solid silicon core; the pore size of the mesoporous layer is 7 to 200 nm (preferably 7 to 100 nm); the specific surface area of the mesoporous layer is 30 to 220.2 m 2 / g.
8. Use of the hydrophilic core-shell silica gel stationary phase according to claim 7 in the chromatographic separation of carbohydrate components.
9. The use according to claim 8, characterized in that A core-shell stationary phase chromatographic column with a hydrophilic shell layer can be used to separate oligosaccharide standards with different polymerization degrees or oligosaccharide components of Morinda officinalis extract or other traditional Chinese medicine oligosaccharide extracts; The processing steps of the Morinda officinalis oligosaccharide sample include the following: (a) The Chinese herbal medicine pieces are crushed into herbal powder by a pulverizer; 10 g of herbal powder is accurately weighed, 100-200 mL of water is added at a solid-liquid ratio of 1:10-20, and the mixture is refluxed at 110-120° C. for 1-6 h, and the filtrate is collected. The herbal residue is again added with 100-200 mL of water and refluxed at 110-120° C. for 2 h, and the filtrates are collected and combined, and the filtrate is concentrated by rotary evaporation to 50-100 mL to obtain a water-extracted concentrate of the herbal medicine; (b) 2 mL of the concentrated aqueous solution was taken and passed through a 0.22-0.45 μm membrane to remove impurities. The solution after passing through the membrane was then loaded onto a graphitized carbon extraction column (the graphitized carbon extraction column was purchased from AMICRON, model: Carb-GCB adsorbent, particle size range: 100-300 mesh, specific surface area 100 m 2 / g, the filling mass is 90-500mg); 2-10mL of 2-5% acetonitrile aqueous solution is passed through the extraction column to remove the monosaccharide components, and finally 2-10mL of 30-50% acetonitrile aqueous solution is used for elution to obtain the Morinda officinalis oligosaccharide extract.
10. The use according to claim 8 or 9, characterized in that The Chinese medicine is one or more of Astragalus, Codonopsis, Morinda officinalis, Asparagus, Crataegus, and Polygala, and the injection volume of the oligosaccharide sample during the chromatographic analysis is 2 to 10 μL; The inner diameter of the hydrophilic core-shell chromatographic column is 2.1-4.6 mm; the column length is one of 50-150 mm, preferably 50-60 mm; The mobile phase A is water without buffer salt, and the mobile phase B can be one or more of acetonitrile, methanol, and ethanol; In the chromatographic separation method, the flow rate is set between 0.3 and 3 mL / min; In the chromatographic separation method, the detector is an evaporative light scattering detector, and the atomizing gas is air; Gas flow rate: 2.5L / min; drift tube temperature is 80~110℃.
Citation Information
Patent Citations
A Rapid Detection Method for Oligosaccharides in Adulterated Honey
CN104215704B
A method for isolating and purifying oligosaccharides from Atractylodes lancea
CN110845638B
Cited By
Modified silicon dioxide microsphere for high performance liquid chromatography and preparation method thereof
CN120420965A
Mesoporous silicon-based composite flocculation material for treating leaching water of steel slag storage yard as well as preparation method and application of mesoporous silicon-based composite flocculation material
CN121699082A